Outbreak of Trypanosoma vivax in Dairy Cattle from São Paulo, Brazil: Haematological and Molecular Diagnostic Approaches - Koether, Karoline [UNESP]; de Albuquerque, Ana L. H. [UNESP]; Zakia, Luiza S.; Rodrigues, Fernanda Panseri [UNESP]; Oliveira-Filho, José P. [UNESP]; Takahira, Regina Kiomi [UNESP]; Borges, Alexandre S. [UNESP]; Lins, José Gabriel G. [UNESP] (MDPI, 2025)
Trypanosoma vivax, a haemoprotozoan of African origin, has spread throughout Latin America, mainly affecting cattle through mechanical transmission by flies. This study reports an outbreak of T. vivax on a dairy farm in the midwestern region of São Paulo State, Brazil. Clinical signs included progressive weight loss, lethargy, hyporexia, reduced milk production, abortions, neurological signs, and deaths. The herd comprised 238 crossbred Holstein-Gir cattle (200 cows, 38 calves). Blood samples were collected from 104 randomly selected cows and all 38 calves to assess hematocrit (HCT) and total plasma protein (TPP), and detect trypomastigote forms using blood and buffy coat smears. PCR was performed on EDTA blood from 30 smear-negative cows. Trypanosoma sp. was identified in 51.9% (54/104) of the smear samples, with morphometric confirmation of T. vivax infection. About 66.6% (20/30) of the smear-negative cows tested positive by PCR, showing the higher sensitivity of molecular tests. Anemia was observed in 56.8% of infected cows, with significantly lower HCT and TPP values than in uninfected animals. The absence of quarantine for new animals, high fly density, and shared needles for oxytocin injections were likely contributing factors. This study underscores the crucial role of molecular diagnostics in accurately investigating outbreaks.